"It cannot be boring!": Developing a measure of function for young adults accessing integrated youth services - Skye Barbic; Emily Brooks; Natalia Lassak; Mo Khaleghi; Marco Zenone; Nikki Ow; Adelena Leon; Steve Mathias (SpringerOpen, 2022)
Abstract Background In Canada, the prevalence of mental health challenges is highest in young people aged 12-24. Mental health challenges frequently cause marked functional impairment. Despite this, we are unaware of any existing conceptualization and/or measures of function that has been developed from the perspective of young people. The objective of this paper is to develop a conceptual and measurement model, including a preliminary set of items, for an outcome measure of function for young adults accessing mental health services. Methods We conducted this study in three phases. In phase 1, we conducted three focus groups to conceptualize function as a construct from the perspective of young adults. In phase 2, we co-designed a set of items with youth (n = 4) to capture the construct. In phase 3, we invited young people (n = 12) accessing mental health services to complete workbooks and participate in one of two focus groups to evaluate whether items were clear, captured function comprehensively, and were relevant. We transcribed and compiled all data to eliminate, refine and generate new items. Results In phase 1, a conceptual model of function was developed with three main themes: basic needs, roles and responsibilities, and social connections. In phase 2, 97 candidate items were developed, and in phase 3, a candidate pool of 50 items resulted for psychometric testing. Conclusion This youth-centred conceptualization of function and preliminary item bank has the potential to advance person-centred care, outcomes, and experiences for youth seeking mental health services.